A COMPREHENSIVE METHODOLOGY FOR NETWORK ASSET IDENTIFICATION AND MAPPING: A COMPREHENSIVE METHODOLOGY FOR NETWORK ASSET IDENTIFICATION AND MAPPING - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This article presents a structured methodology for network asset discovery and mapping, combining both passive and active reconnaissance techniques. The framework strategically employs specialized tools, such as p0f for passive OS fingerprinting and Netdiscovery for initial host enumeration, to build a foundational network map while minimizing the risk of triggering alerts. Deeper information gathering is performed using the Dmitry toolkit, and Amap is applied for advanced service and application protocol detection on identified ports. The methodology is further enhanced through Etherape, which provides real-time visualization of network traffic, allowing correlation between observed flows and actively collected data. A case study demonstrates the effectiveness of this integrated approach, showing a more complete and accurate network asset inventory compared to traditional, non-integrated tool usage.